Guidance for Students in The Development of Learning Media to Increase Learning Outcomes - Matje, Irman (Lembaga Riset dan Inovasi Masyarakat Madani, 2022)
Overcoming the problem of low student learning outcomes is very important for the development of learning media so that students get good learning outcomes. Therefore, this study aims to determine the development of learning media to improve social studies learning outcomes. The population in this study were all students of class V as many as 22 students. The total value of the learning media development test on student learning outcomes is 0.81, in accordance with the findings of this study that the impact index value obtained is positive. The development of learning media has a significant effect on student learning outcomes. The development of learning media is considered successful if it is able to actively involve students in the learning process physically, mentally, and socially, as well as increase students' self-confidence.